Kendala dalam Proses Pemberdayaan Masyarakat di Balai Latihan Kerja Komunitas Pondok Pesantren Darul Makmur Sungai Cubadak - Nabilla, Intan; Alhadi, Zikri (PUBLICNESS: Journal of Public Administration Studies, 2024)
Job training is a community empowerment effort carried out by the government in order to shape people into workers who have competence and are ready to enter the world of work. In carrying out training, there will definitely be several obstacles that hinder the training process from running optimally. So research was conducted to determine the obstacles in community empowerment efforts at the Darul Makmur Sungai Cubadak Islamic Boarding School Community Job Training Center through job training. This research uses a qualitative approach with descriptive methods. The data collection techniques used were interview and documentation methods. The results of the research show that there are obstacles that hinder the community empowerment process at the Darul Makmur Sungai Cubadak Islamic Boarding School Community Work Training Center, consisting of internal obstacles and external obstacles.